AB0890 EFFECT OF DIFFERENT TYPES OF URIC ACID-LOWERING DRUGS ON GOUT ATTACK. (June 2019) - Wang, Ya-Ling; Lin, LI; Tao, Jinhui; Tang, Yu-Jie; Lu, Qun-Qun; Zhang, Hong-Liang; Zhu, Zi-Wen
Abstract : Background: Gout is an inflammatory arthritis associated with hyperuricemia which is caused by purine metabolism disorders. General uric acid lowering treatment sometimes causes the onset of gout, but the specific cause is not clear. Our group has found that adenine nucleoside triphosphate (ATP) plays an important role in the pathogenesis of gout. It synergizes with MSU to stimulate the secretion of IL-1β, leading to the onset of gout. [1, 2] The xanthine oxidase inhibitors promote the production of ATP, while the drugs that promotes the excretion of uric acid does not affect ATP production. Therefore, we speculate that gout attacks induced by allopurinol and febuxostat are related to the role that ATP plays in the pathogenesis of gout. Objectives: To compare the effects of drugs that inhibit uric acid production and promote uric acid excretion on gout. Methods: A case-control study was used to compare the changes in serum uric acid concentration and observe whether the patients would suffer gouty arthritis within one month. The gout patients complied with the standard that the number of gout attacks did not exceed three times, as well as more than one time within the past six months, were selected. And patients with other chronic inflammatory and infectious diseases were excluded. Results: A total of 148 patients with gout in the Department of Rheumatology and Immunology of Anhui Provincial Hospital were collected, all of whom were male. According to the patients taking uric acid-lowering drugs, they were divided into four groups: group A: control group (no uric acid-lowering treatment, n=35); group B: febuxostat group (40 mg Qd, n=66); group C: allopurinol group (0.1 g Bid, n=11); group D: benzbromarone group (50mg Qd, n=36). The statistical results are as follows: (1) The levels of serum uric acid in group B, C and D were significantly decreased after uric acid-lowering treatment compared with those before treatment (B: 389.6±88.9 vs 547.5±93.0, C:363.3±28.6 vs 504.0±38.3, D: 376.2±108.5 vs 557.3±101.8) within one month, and there was no significant difference in the level of uric acid before uric acid-lowering treatment among the three groups. (2). Comparison of gouty arthritis recurrence rates: The recurrence rate of gout patients in group B was 33.3%, and was 18.2% in group C, which was significantly higher than that in group D (11.1%), the difference was statistically significant ( P <0.05); the recurrence rate of gout patients in group A was 14.3%, and there was no significant difference compared with group D (P>0.05); the recurrence rate of gout patients treated by drugs that inhibited uric acid production (B+C group) was 31.2%, which was significantly higher than patients treated by drugs that promoted uric acid excretion (D group) 11.1%, the difference was statistically significant ( P <0.05). Conclusion: Under the same uric acid-lowering intensity, the drugs that inhibit uric acid production can induce gout attacks during the process of uric acid lowering, while the drugs that promote uric acid excretion has less effect on the recurrence of gouty arthritis. References: [1] Tao JH, et al. P2X7R: A potential key regulator of acute gouty arthritis. Semin Arthritis Rheum. 2013; 43(3): 376-380. [2] Tao JH, et al. Single nucleotide polymorphisms associated with P2X7R function regulate the onset of gouty arthritis. PLoS One. 2017Aug10;12(8):e0181685. Acknowledgement: This work was supported by grants from the National Natural Science Foundation of China (81771774) and the Anhui Provincial Natural Science Foundation (1708085MH191) Disclosure of Interests: None declared